A Historical Review of Pavement Management Approaches Employed in Nepal - Shrestha, Saurav; Kunwar, Deepak Bahadur; Shrestha, Aadarsha Ram; Kafle, Shesh Raj; Amgain, Arbin (International Journal on Engineering Technology and Infrastructure Development, 2025)
Pavement management in Nepal has evolved over the past several decades through intertwined technical, institutional, and technological developments. This paper presents a comprehensive historical review of Nepal’s pavement management approaches, highlighting: (1) technical advancements in performance modelling from simple empirical deterioration models to Markovian hazard-based models and modern AI/ML techniques alongside the use of pavement condition indices (SDI, IRI, PCI) in the Nepali context; (2) institutional and policy evolution, including the establishment of Roads Board Nepal (RBN) in 2002 to ensure sustainable maintenance funding, development of planning guidelines focusing on a Surface Distress Index (SDI) rating, and the crucial role of international donors (World Bank, JICA) in capacity building and system development; and (3) technology adoption trends, from the introduction of the Highway Development and Management (HDM-4) tool and a Highway Management Information System (HMIS) for data-driven planning, to recent integration of GIS-based Road Asset Management Systems (RAMS) and innovative data collection via smartphone applications like RoadRoid. Through extensive literature survey, we synthesize how technical methodologies have improved, how policies and institutions have adapted, and how new technologies are being embraced. The findings reveal a trajectory of progress: from subjective visual indices and ad-hoc repairs towards data-driven, long-term asset management planning. Nonetheless, challenges remain in fully institutionalizing advanced models and tools amid resource constraints. Recommendations are provided for strengthening pavement management in Nepal by integrating modern predictive models, enhancing institutional capacity, and leveraging appropriate technologies for sustainable road network performance.